6,6′-(Pyridine-2,6-diyl)bis(pyrrolo[3,4-b]pyridine-5,7-dione) - P. C. W. Van der Berg; Hendrik G. Visser; Andreas Roodt (Acta Crystallographica Section E, 2011)
The title compound, C19H9N5O4, has crystallographically imposed twofold rotational symmetry. The asymmetric unit contains one half-molecule. The crystal structure is stabilized by π–π stacking of inversion-related pyrrolo[3,4-b]pyridine rings, with a centroid–centroid distance between stacked pyridines of 3.6960 (8) Å. The dihedral angle between the central pyridine ring and the pyrrolo-pyridine side rings is 77.86 (2)° while the angle between the two side chains is 60.87 (2)°.